2018
DOI: 10.1111/jocd.12707
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel PLCD1 mutation in Chinese Han pedigree with hereditary leukonychia and koilonychia

Abstract: For the first time, a hereditary leukonychia case with PLCD1 mutation has been described in Chinese Han pedigree. This finding suggests the PLCD1 mutation maybe involved in hereditary leukonychia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A number of genetic studies of patients with hereditary leukonychia support an association with mutations in the PLCD1 gene [325][326][327][328][329]. Hereditary leukonychia is a nail disorder characterised by nail plates whitening on all finger and toe nails referred to as porcelain nails.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…A number of genetic studies of patients with hereditary leukonychia support an association with mutations in the PLCD1 gene [325][326][327][328][329]. Hereditary leukonychia is a nail disorder characterised by nail plates whitening on all finger and toe nails referred to as porcelain nails.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Moreover, it was found that the clinical manifestations of leukonychia concomitant koilonychias did not merely occur in the family described herein. The condition has also been reported in few cases of Chinese and Pakistani families (9,(13)(14)(15). Thus, this phenomena may not be a result of ethnic differences.…”
Section: Discussionmentioning
confidence: 75%
“…After reviewing the literature related to hereditary leukonychia, it was found that mutations in five genes are linked to the pathogenesis of HL (9). Different genes may be associated with distinct clinical phenotypes of HL.…”
Section: Discussionmentioning
confidence: 99%
“… 1 In another study examining HL in a Chinese Han pedigree with 2 affected individuals (mother and son), whole-exome sequence analysis identified a new missense mutation in exon 9 of the PLCD1 gene ( Table I ). 2 …”
Section: Discussionmentioning
confidence: 99%
“…Hereditary leukonychias (HLs) are rare nail disorders that present with partial or complete nail plate whitening, 1 , 2 due to abnormal keratinization of distal nail matrix cells, with numerous intracellular vacuoles with less dense keratin that appear white with light reflection. 2 Some cases are due to Phospholipase C, delta-1 (PLCD1) gene mutations, encoding an enzyme regulating energy metabolism signaling, Ca 2+ homeostasis, and intracellular movement. 1 We present a case of leukonychia associated with a novel homozygous missense PLCD1 gene mutation.…”
Section: Introductionmentioning
confidence: 99%